Interview with Professor Yolanda A. Patterson - Sapere Aude, Revista (Sapere Aude, 2013)
Interview with Professor Yolanda A. Patterson. She's emerita Professor of French and Women’s Studies for the California State University-Hayward, USA, as well as President of the Simone de Beauvoir Society. Selected Publications: Simone de Beauvoir and the Demystification of Motherhood. Yale French Studies.